The Impact of Standing Regional Cervical Sagittal Alignment on Outcomes in Posterior Cervical Fusion Surgery. (30th May 2012) - Tang, Jessica A.; Scheer, Justin K.; Smith, Justin S.; Deviren, Vedat; Bess, Shay; Hart, Robert A.; Lafage, Virginie; Shaffrey, Christopher I.; Schwab, Frank; Ames, Christopher P.
Abstract: BACKGROUND: Positive spinal regional and global sagittal malalignment has been repeatedly shown to correlate with pain and disability in thoracolumbar fusion. OBJECTIVE: To evaluate the relationship between regional cervical sagittal alignment and postoperative outcomes for patients receiving multilevel cervical posterior fusion. METHODS: From 2006 to 2010, 113 patients received multilevel posterior cervical fusion for cervical stenosis, myelopathy, and kyphosis. Radiographic measurements made at intermediate follow-up included the following: (1) C1-C2 lordosis, (2) C2-C7 lordosis, (3) C2-C7 sagittal vertical axis (C2-C7 SVA; distance between C2 plumb line and C7), (4) center of gravity of head SVA (CGH-C7 SVA), and (5) C1-C7 SVA. Health-related quality-of-life measures included neck disability index (NDI), visual analog pain scale, and SF-36 physical component scores. Pearson product-moment correlation coefficients were calculated between pairs of radiographic measures and health-related quality-of-life scores. RESULTS: Both C2-C7 SVA and CGH-C7 SVA negatively correlated with SF-36 physical component scores ( r = − 0.43, P< .001 and r =− 0.36, P = .005, respectively). C2-C7 SVA positively correlated with NDI scores ( r = 0.20, P = .036). C2-C7 SVA positively correlated with C1-C2 lordosis ( r = 0.33, P = .001). For significant correlations between C2-C7 SVA and NDI scores, regression models predicted a threshold C2-C7 SVA value of approximately 40 mm, beyond which correlations were most significant. CONCLUSION: Our findings demonstrate that, similar to the thoracolumbar spine, the severity of disability increases with positive sagittal malalignment following surgical reconstruction.